Paul Maenz Jahresbericht 1973 Köln & Brüssel : Askevold - Atkinson - Baldwin - Barry - Burgin - Burn etc. - Paul Maenz, Köln; Paul Maenz, Brussel (Köln : Paul Maenz, 1973)
Askevold, David ; Atkinson, Terry ; Baldwin, Michael ; Barry, Robert ; Burgin, Victor ; Burn, Ian ; Feldmann, Hans-Peter ; Haacke, Hans ; Kawara, On ; Kosuth, Joseph ; Manzoni, Piero ; Penone, Giuseppe ; Pilkington ; Poirier, Anna & Patrick ; Ramsden, Mel ; Roehr, Peter; Rushton ; Salvo ; Wery, Marthe ; Art & Language
Duits
boek